Application of Scales and Questionnaires to Assess the State of Patients After Stroke - Majidova E.N; Belova L.A; Khusenova N.T; Bakhramov M.S; Yuldasheva M.M; Isamukhamedova U.R (Genius Journals, 2023)
Acute cerebrovascular accident (ACC) is one of the most urgent problems of modern medicine and healthcare. To assess the condition of patients, it is necessary to apply certain evaluation systems - scales. The article describes the results of a study of 85 patients with stroke. A correct understanding of the condition of each patient made it possible to reasonably set strategic and tactical goals of treatment, to weigh the potential risks and benefits of individual methods of treatment in cases where the patient's condition is extremely serious and the probability of death is high. The use of scales in the practice of a neurologist makes it possible to increase the efficiency of decision-making in matters of therapy, the effectiveness of predicting stroke outcomes, and to compare treatment methods
Keywords: stroke; quality of life; Barthel index; Waterlow scale; MMSE scale